Minimally Invasive Robotic-Assisted Cystolithotomy in a Complicated Urinary Diversion: A Feasible and Safe Approach - A. Haffar; C. Crigger; T. Trump; M. Jessop; M. W. Salkini (Case Reports in Urology)
Urinary diversion following radical cystectomy and neoadjuvant chemotherapy is the gold standard for the management of muscle-invasive bladder cancer. Urinary diversions are at an increased risk of urolithiasis as a result of various factors. Traditional surgical intervention has included open cystolithotomy which has given way to minimally invasive techniques as of late. We describe a case of a robotic-assisted cystolithotomy from a neobladder in a 54-year-old female patient with muscle-invasive bladder cancer. This is the first description of a robotic-assisted removal of a stone in an orthotopic neobladder. This approach has many advantages, especially in the removal of larger stones. Further study is needed to investigate the efficacy and success of this approach.